Kształtowanie się struktury administracyjnej prawosławnej diecezji wrocławsko-szczecińskiej po II wojnie światowej = The development of the administration structure of the ortodox diocese of Wrocław-Szczecin after World War II - Dudra, Stefan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Wrocław-Szczecin diocese was established on Seprember 7, 1951, and comprised thethen states of Koszalińskie, Szczecińskie, Wrocławskie, and Zielonogórskie. Its establishmentwas connected with the "Wisła" resettlement campaign of 1947. The first Orthodox parishes, however, were set up immediately afrer World War II had ended and were grouped in two deaneries: Wrocław and Szczecin. The diocese's parish network formed mainly over the period of 1947-1958.
Keywords: kościół prawosławny; Polska - historia - od 1944 r.; administracja kościelna; prawosławna diecezja wrocławsko-szczecińska